Report on Proceedings of the 19th Annual Meeting of the Global Alliance for Medical Education, Coral Gables, Florida, USA, 18–20 May 2014. Issue 1 (1st January 2014) - Murray, Ron
Abstract : Participants from North, South, and Central America; Europe; Asia; and Australia attended the 19th annual meeting of the Global Alliance for Medical Education in Coral Gables, Florida, the United States between 18 and 20 May 2014. The educational and networking sessions focused on the impact of technology, research, and innovative approaches in continuing medical education and continuing professional development (CME/CPD). A series of invited presentations dealt with medical education research, web-based patient engagement tools, international professional communities, an integrated health information system supporting educational strategies, and the integration of Evidence-Based Medicine and Best Evidence Medical Education to improve outcomes. The invited presentations were supplemented by panel discussions, a competitive game on global CME/CPD knowledge, and abstract presentations on a range of projects being carried out in some of the countries represented at the meeting.